Gry pamięci. Valiant Hearts: The Great War i My Memory of Us w perspektywie kultury historycznej - Pigulak , Marcin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The paper aims to outline how video games Valiant Hearts: The Great War (Ubisoft Montpellier, 2014) and My Memory of Us (Juggler Games, 2018) use narrative and ludic structures to create commemorative stories about the First World War and the Second World War. The author refer to the concept of historical culture (among others, in Jörn Rüsen’s interpretation) and examine the connections between the two video games focusing on the issue of designers’ intentions (digital games as examples of the commemoration of the past), the genre similarity (2D platform games), the intermedial convergence and the press reception. He discusses the strategy of the cultural agreement between designers and users, analyzes historical narratives as a part of the gameplay, examines relations between the individual and collective’s perspective and characterizes immersion’s mechanisms which reinforce players’ identification with the victims of both wars.